Evaluation and Utility of a Family Information Table to Identify and Test Children at Risk for HIV in Kenya - Michelle Meyer, BA; Molly Elmer-DeWitt, BA; Cinthia Blat, MPH; Starley B. Shade, PhD; Ijaa Kapule, MBChB, PhD; Elizabeth Bukusi, MBChB, PhD; Craig R. Cohen, MD; Lisa Abuogi, MD (Global Health and Education Projects, Inc., 2014)
Background: Effective strategies to identify and screen children at risk for HIV are needed. The objectives of this study were to evaluate the utilization of a family information table (FIT) to identify and test at-risk children in Kenya and identify factors associated with child testing. Methods: A cross-sectional study was conducted among HIV-infected adults with children at five Kenyan clinics. HIV testing status for children aged ≤18 years was gathered from the patients' FITs and compared to reports from in-person clinic visits as the gold standard. Generalized estimating equations were used to assess predictors for HIV testing of children adjusted for confounders and within parent correlation. Results: Our sample included 384 HIV-infected adults enrolled in care with 933 reported children. Overall, 323 FITs (84%) correctly listed all children in the family and 340 (89%) documented an HIV testing status (including untested) for all children. Seventy-five percent of parents verbally reported all children tested, compared to only 46% of FITs (OR=13.5, 95% CI 6.5-27.8). Verbal reports identified 739 (79%) children tested, with 55 (7.4%) HIV-positive and 17 (2.3%) HIV-exposed infants (HEI). Of 63 adults with HIV-positive children or HEI, 60 (95%) reported enrolling children into care. Likelihood that children had been tested was higher for younger children (≤4y vs. > 4y, aOR=2.0; 95% CI 1.4-2.9) and lower if the partner's serostatus was unknown vs. seropositive (aOR=0.3; 95% CI: 0.1-0.8). Conclusions: Although the FIT may be a useful tool to identify children at risk for HIV, this study found underutilization by providers. To maximize impact of this tool, documentation of follow-up for untested and positive children is essential. Global Health Implications: Through early documentation of at-risk children and follow up of untested and infected children, the FIT may serve as an effective resource for improving HIV testing and linkage to care. Key Words: Family Information Table • Pediatrics • HIV/AIDS • Linkage • Kenya • HIV Testing Copyright © 2014 Meyer et al. This is an open-access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.